MiR-328 targeting PIM-1 inhibits proliferation and migration of pulmonary arterial smooth muscle cells in PDGFBB signaling pathway - Qian, Zhengjiang (Oncotarget, 2016)
MicroRNAs (miRNAs) have been recognized to mediate PDGF-induced cell dysregulation, but their exact functions remain to be elucidated. By using a sensitive S-Poly(T) Plus qRT-PCR method, the expression profiling of 1,078 miRNAs were investigated in pulmonary artery smooth muscle cells (PASMCs) with or without PDGFBB stimulation. MiR-328 was found as a prominent down-regulated miRNA, displaying a specific dose- and time-dependent downregulation upon PDGFBB exposure. Functional analyses revealed that miR-328 could inhibit PASMCs proliferation and migration both with and without PDGFBB treatment. The Ser/Thr-protein kinase-1 (PIM-1) was identified as a direct target of miR-328, and functionally confirmed by a rescue experiment. In addition, the decrease of miR-328 by PDGFBB might be due to the increased expression of DNA methylation transferase 1 (DNMT1) and DNA methylation. Finally, serum miR-328 level was downregulated in PAH patients associated with congenital heart disease (CHD- PAH). Overall, this study provides critical insight into fundamental regulatory mechanism of miR-328 in PDGFBB-activited PASMCs via targeting PIM- 1, and implies the potential of serum miR-328 level as a circulating biomarker for CHD- PAH diagnosis.